THE IMPACT OF SOCIAL MEDIA USE ON EDUCATIONAL MANAGEMENT AND COMMUNICATION WITH STUDENTS AND PARENTS - Rabia Sana; Rabia Mahmood; Rodolfo Jr F. Calimlim; Qaisar Ali Khan; Komal Akbar (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the impact of social media use on educational management and communication with students and parents, focusing on the challenges it presents. Utilizing a sample size of 305 students, the research employs a quantitative approach with a self-made tool designed to measure the effects of social media on school administration, teacher-student interaction, and parent-teacher communication. The findings reveal a significant negative impact of social media use on educational management. Increased reliance on social media platforms led to a reduction in the effectiveness of traditional communication channels, resulting in decreased engagement and understanding between educators, students, and parents. The study also highlights issues related to the miscommunication, distractions, and misinformation spread through social media, which contribute to a decline in the quality of educational interactions. The overuse of social media by students was found to hinder their academic performance and participation in activities. Furthermore, parents’ dependence on social media for updates often resulted in a fragmented understanding of their child’s educational progress. These results underscore the need for a more structured and balanced approach to integrating social media into educational practices, ensuring that it supports rather than undermines effective communication and management. The study calls for future research to explore strategies that can mitigate these negative effects while enhancing the benefits of social media in educational contexts.